PENGETAHUAN IBU HAMIL DAN DUKUNGAN KELUARGA PADA KEJADIAN KEHAMILAN USIA MUDA REMAJA - Andriana, Kiki; Diniyati, Taty Nurti, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Unwanted teenage pregnancies are very embarrassing and can damage theirfuture, therefore some teenagers have an abortion to abort their pregnancy. This researchis an analytical research using Cross Sectional approach. The study population was allpregnant women from July to September as many as 370 pregnant women. The sample inthis study were 82 respondents. The sampling technique was carried out by means ofquata sampling. Data collection was carried out by filling out the questionnaire carriedout on October 23 to November 2, 2017. Data analysis was used chi-square with p-value0.005. The results showed that most respondents did not experience pregnancy at a youngage, lacked knowledge and had negative family support. Based on the results of theanalysis there is a significant relationship between knowledge and family support with theincidence of pregnancy at a young age with p-value, namely p = 0.033 and p = 0.030.Respondents' knowledge can be improved by conducting counseling, disseminatingfanplet, health promotion, and activeness of respondents seeking information aboutpregnancy at a young age, attending formal or non-formal health education namelyconsulting with health workers and respondents can seek information through print andelectronic media.